Surface-Enhanced Oxidation and Determination of Isothipendyl Hydrochloride at an Electrochemical Sensing Film Constructed by Multiwalled Carbon Nanotubes - S. N. Prashanth; Shankara S. Kalanur; Nagappa L. Teradal; J. Seetharamappa (International Journal of Electrochemistry)
The electrochemical behavior of isothipendyl hydrochloride (IPH) was investigated at bare and multiwalled-carbon-nanotube modified glassy carbon electrode (MWCNT-GCE). IPH (55 μM) showed two oxidation peaks in Britton-Robinson (BR) buffer of pH 7.0. The oxidation process of IPH was observed to be irreversible over the pH range of 2.5–9.0. The influence of pH, scan rate, and concentration of the drug on anodic peak was studied. A differential pulse voltammetric method with good precision and accuracy was developed for the determination of IPH in pure and biological fluids. The peak current was found to be linearly dependent on the concentration of IPH in the range of 1.25–55 μM. The values of limit of detection and limit of quantification were noticed to be 0.284 and 0.949 μM, respectively.